Treatment of Iron Deficiency in Women - Breymann, C.; Römer, T.; Dudenhausen, J. W. (Geburtshilfe und Frauenheilkunde, 2013)
Iron deficiency with and without anaemia is a common cause of morbidity, particularly in women. Iron deficiency is generally the result of an imbalance between iron loss and iron absorption. In women with symptoms suspicious for iron deficiency, it is important to confirm or exclude the suspicion using proper tests. The use of serum ferritin levels is considered the gold standard for diagnosis. Although the ideal ferritin levels are not unknown the current consent is that levels < 40 ng/ml indicate iron deficiency, which needs to be treated in symptomatic patients. However, symptoms can already occur at ferritin levels of < 100 ng/ml and treatment must be adapted to the individual patient. Iron supplementation is only indicated in symptomatic patients diagnosed with iron deficiency whose quality of life is affected. It is important to treat iron deficiency together with its causes or risk factors. For example, blood loss from hypermenorrhea should be reduced. Women also need to receive information about the benefits of an iron-rich diet. If oral treatment with iron supplements is ineffective, parenteral iron administration is recommended.
Keywords: biomarker; epidemiology; uterus